Trade-Environment Nexus in Environmental Kuznets Curve Hypothesis Framework: A Time Series Study for Uzbekistan - Haq, Ihtisham Ul; Nurmatov, Norbek; Allayarov, Piratdin; Tajibaeva, Kizlargul; Khalekeeva, Zoya (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of trade on environmental degradation in Uzbekistan. However, to capture the individual effect of exports and imports, this study includes exports openness and imports openness as factors of environmental degradation. Moreover, this study also examines the environmental Kuznets curve (EKC) hypothesis. Thus, these two objectives make this study unique for Uzbekistan. This study determined cointegration through bounds test approach. Moreover, one can also capture short run and long run effects through this Bounds approach. The results of this study show that exports openness has a negative but insignificant effect on environmental degradation, whereas imports openness has a positive and significant effect on environmental degradation. These results demonstrate that negative effects of exports openness is not upsetting the deteriorating effect of imports openness therefore, it is concluded that trade is leading to environmental degradation in Uzbekistan. Additionally, the result of this study confirms EKC hypothesis in Uzbekistan.